Impact of intracytoplasmic sperm injection in women with non-male factor infertility: A systematic review and meta-analysis - Huang, Jun-Xia; Gao, Yu-Qi; Chen, Xiao-Tong; Han, Ying-Qi; Song, Jing-Yan; Sun, Zhen-Gao (Frontiers in Reproductive Health, 2022)
Objective The purpose of this study is to determine whether intracytoplasmic sperm injection (ICSI) is beneficial in patients with non-male factor infertility. Methods This systematic review and meta-analysis included articles from inception to May 2022. Published studies of non-male factor infertile women undergoing ICSI or in vitro fertilization (IVF) included in PubMed, Embase, web of science, Wanfang Database, and CNKI were searched by computer, without language restrictions. A random-effect model was applied to calculate the risk ratios (RRs) and their 95% confidence intervals (CIs). Letters, case reports, and review articles including meta-analyses and expert opinions were excluded. The primary endpoints were laboratory outcomes and pregnancy outcomes. The Secondary endpoints were neonatal outcomes. Results Six randomized controlled studies and 20 retrospective cohort studies met the inclusion criteria. In meta-analytic forest plots, compared with IVF, those who received ICSI treatment were not different in fertilization rate (RR = 0.99, 95% CI [0.90–1.09], P = 0.88), total fertilization failure rate (RR = 1.30, 95% CI [1.17–1.45], P < 0.00001), and good quality embryo rate (RR = 0.94, 95% CI [ 0.86–1.02], P = 0.15), clinical pregnancy rate (RR = 0.84, 95% CI [0.70–1.01], P = 0.06), live birth rate (RR = 0.89, 95% CI [0.77–1.03], P = 0.13), miscarriage rate (RR = 1.06, 95% CI [0.78–1.43], P = 0.71), preterm neonatal delivery rate (RR = 0.92, 95% CI [0.67–1.26], P = 0.61), and low neonatal weight rate (RR = 1.13, 95% CI [0.80–1.61], P = 0.48). However, the implantation rate of IVF was better than ICSI (RR = 0.77, 95% CI [0.64–0.93], P = 0.005). In the subgroup analysis of the live birth rate of fresh embryo transfer, IVF performed in those ≥35 years had a higher live birth rate (RR = 0.82, 95% CI [0.78–0.83], P < 0.001). Conclusion The findings of this study indicate that ICSI is not superior to IVF in the treatment of infertility related to non-male factors. In order to confirm this result, more high-quality clinical studies are needed.